Interactive effects of fertilizer and inoculum concentration on subsequent development of xanthomonas wilt in banana - Ochola, D.; Ocimati, W.; Tinzaara, William; Karamura, E.B. (Academic Journals, 2014)
Soil nutrient depletion and Xanthomonas wilt (Xanthomonas campestris pv. musacearum) are major causes of declining productivity in smallholder banana systems in East and Central Africa. This study examined the interactive effect of fertilizer and inoculum concentration on development of Xanthomonas wilt. Fertilization significantly (p<0.01) increased the plant height, plant girth and leaf area in banana compared to control without fertilizer. Despite this, between 9 and 21 days post inoculation (dpi) all inoculated plants had exhibited typical disease symptoms (that is, chlorosis, necrosis and wilting of leaves). No significant reduction (p>0.05) in disease incidence, wilt severity index or mortality could be associated with increasing fertilizer amounts. Interestingly, there was a highly significant (p<0.01) overriding effect of inoculum concentration on the ability of fertilizer to reduce wilt severity index and mortality in banana. Plants inoculated with 106 to 1012 cfu mL-1 developed twice as much disease compared to 104 cfu mL-1 inoculations. Average mortality of 9.2% for 104 cfu mL-1 inoculated plants provides evidence of the potential to cause latent infections. Low bacterial loads are implicated in recent field resurgence of Xanthomonas wilt in banana orchards where disease had been successfully contained.